Career & technical education [electronic resource] (MERLOT, 2020)
Quoted from the homepage:ePortfolios and Career & Technical Education: SkillsCommons has used multiple methods for capturing open educational practices in teaching, learning, and institutional ePortfolios. Structured video and podcast interviews with CTE program leaders to explain the innovations and successes of their workforce development programs. Storytelling methods that SkillsCommons customized for capturing the impact of innovations and successes of their workforce development programs. Reuse, Revise, & Remix strategies and examples showcasing open educational practices by CTE programs. Partner with commercial providers to reuse, revise, remix OER and improve the quality of learning experiences and outcomes. Explore the collection of over 50 institutional and teaching video and podcast ePortfolios that tell CTE stories of how, what, and why they changed to more innovative and successful learning and employability solutions for their diverse populations of students.